The Economic Ascent of the Hotel Business / Second Edition - Slattery Paul (Goodfellow Publishing, 2012)
This book is about the hotel business and the economic contexts in which it has evolved. Preface, Acknowledgements, Economic Structure, Historic Agricultural Economies and the Hotel Business to 1750, The Industrial Revolution and the Hotel Business: 1750-1900, Economic Developments and the Hotel Business: 1850-1900, Critical Events and the Hotel Business: 1900-1945, The US Economic Structure and Hotel Business: 1945-1960, European Economic Structures and Hotel Businesses: 1945-1960, The US Economic Structure and Hotel Business: 1960-1980, The European Economies and Hotel Businesses: 1960-1980, The US Hotel Business: 1980-2010, The British Hotel Business: 1980-2010, Continental European Hotel Businesses: 1980-2008, The Economic Ascent of the Hotel Business: Options to 2020, Bibliography, Websites, Index.